2012
DOI: 10.1007/s11011-012-9309-7
|View full text |Cite
|
Sign up to set email alerts
|

Developmental traumatic brain injury decreased brain derived neurotrophic factor expression late after injury

Abstract: Pediatric traumatic brain injury (TBI) is a major cause of acquired cognitive dysfunction in children. Hippocampal Brain Derived Neurotrophic Factor (BDNF) is important for normal cognition. Little is known about the effects of TBI on BDNF levels in the developing hippocampus. We used controlled cortical impact (CCI) in the 17 day old rat pup to test the hypothesis that CCI would first increase rat hippocampal BDNF mRNA/protein levels relative to SHAM and Naïve rats by post injury day (PID) 2 and then decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 40 publications
1
22
0
2
Order By: Relevance
“…Comparably, BDNF protein levels, measured by reverse phase protein microarray, increased in rat injured brains, and no significant level variations were reported over 2 weeks following the injury (Rostami et al, ). In contrast, mild severity level of TBI obtained by lateral percussion displayed unchanged BDNF mRNA levels in hippocampal homogenates of 17 days old rat pups (Schober, Block, Requena, Hale, & Lane, ).…”
Section: Discussionmentioning
confidence: 99%
“…Comparably, BDNF protein levels, measured by reverse phase protein microarray, increased in rat injured brains, and no significant level variations were reported over 2 weeks following the injury (Rostami et al, ). In contrast, mild severity level of TBI obtained by lateral percussion displayed unchanged BDNF mRNA levels in hippocampal homogenates of 17 days old rat pups (Schober, Block, Requena, Hale, & Lane, ).…”
Section: Discussionmentioning
confidence: 99%
“…Double labeling studies showed that a subpopulation of CD68-immunoreactive microglia/macrophage co-expressed BDNF in the cortex and spinal cord, and also TrkB[gp145] or TrkB[TK-] in the spinal cord; whereas cytokine expression of TNF-α, IL-6, and IL-1-β was less prominent at the 1, 6, and 12-month intervals, suggesting that immediate inflammatory responses had subsided (Nagamoto-Combs et al, 2007). Yet, in a CCI rat model there is a decline in BDNF-mRNA and protein levels measured at 1–14 days post injury (Schober et al, 2012). Moreover, specific BDNF polymorphisms may not be involved in TBI pathology (Bagnato et al, 2012).…”
Section: Harnessing Microglial Pro-survival Functionsmentioning
confidence: 99%
“…There is evidence that upregulation of BDNF reduces the impact of secondary injury following TBI (Kaplan et al, 2010). However, there might be decreases in BDNF with increased time since injury, resulting from tissue loss over the first year post-injury (Schober, Block, Requena, Hale, & Lane, 2012). Previous work suggests a causal link between BDNF expression during wakefulness and subsequent slow-wave activity (SWA) during sleep (Faraguna et al, 2008).…”
Section: Sleep Disturbances Following Traumatic Brain Injurymentioning
confidence: 99%